“ANNIHILATION OF THE HEART”: THE IDEAL OF NON-PERCEPTION IN THE LIEZI. - Sage, Richard J. (Problems / Problemos)
The early Chinese text Liezi列子 claims that you have to modify your perceptive faculties in order to unify your full shen 神 (“spirit”) and become a zhi ren 至人– an “utmost human”, able to get in touch with the primordial cosmic forces, and endowed with special skills and properties. The idea that the proper adjustment of your perception leads to this state is deeply rooted within the Liezi’s view on the evolution of the cosmic and social order. In fact, the work describes the gradual modification of the perceptive process in a way that it is possible to juxtapose it with the cosmogony expounded in its first chapter. The aim of this paper is thus to analyse these processes, clarify how they are related to each other and explore what it ultimately means to become an “utmost human”. In the end it becomes clear that only the complete obliteration of perception, including the xin 心 (“heart”) as its main actor, makes the “utmost human” able to become one with the primordial forces and gain their powers.